Women and the Justice Divide in Asia Pacific: How can Informal and Formal Institutions Bridge the Gap? - Mollica, Caitlin; Davies, Sara E.; True, Jacqui; Eddyono, Sri Wiyanti; Fonseka, Bhavani; Johnston, Melissa (Johns Hopkins University Press, 2022)
Across Asia and the Pacific, legal pluralist systems meet both cultural norms and address injustices at the local level. What is the capacity of these pluralist systems to provide justice and mitigate discrimination against women? This article examines women’s experiences across five countries to identify the factors that enable and constrain women’s engagement with legal pluralist justice systems in the Asia-Pacific region. Drawing on examples of women’s individual and collective attempts to access justice specifically concerning custody, land, and violence, this article identifies three persistent conditions that perpetuate women’s inability to access justice: the absence of gender mainstreaming resources in pluralist legal systems, most notably in rural, remote, and impoverished communities; cultural and religious preference for women’s underrepresentation in decision-making; and women’s low representation in justice-related civil service positions.